2013
DOI: 10.1111/liv.12353
|View full text |Cite
|
Sign up to set email alerts
|

Mixed lineage kinase 3 deficient mice are protected against the high fat high carbohydrate diet‐induced steatohepatitis

Abstract: Background C-Jun N-terminal kinase (JNK) activation is pivotal in the development of nonalcoholic steatohepatitis (NASH). Mixed lineage kinase 3 (MLK) 3 is one of the mitogen activated protein kinase kinase kinase (MAP3K) that mediates JNK activation in the liver. Despite this concept, the role of MLK3 in modulating liver injury during nutrient excess has not been explored. Aims our aim was to determine if MLK3 deficient mice were protected against high fat high carbohydrate (HFHC) diet-induced NASH. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 44 publications
(70 reference statements)
1
52
0
Order By: Relevance
“…1) (6). LPC can activate proapoptotic signaling akin to palmitate (6,16), and lead to extracellular vesicle (EV) release (24). Palmitatederived C16:0 ceramide is associated with insulin resistance and steatohepatitis (25,26), and at a cellular level can induce EV release (27).…”
Section: Free Fatty Acid-induced Proapoptotic Signaling By Death Recementioning
confidence: 99%
See 1 more Smart Citation
“…1) (6). LPC can activate proapoptotic signaling akin to palmitate (6,16), and lead to extracellular vesicle (EV) release (24). Palmitatederived C16:0 ceramide is associated with insulin resistance and steatohepatitis (25,26), and at a cellular level can induce EV release (27).…”
Section: Free Fatty Acid-induced Proapoptotic Signaling By Death Recementioning
confidence: 99%
“…Lipid-induced activation of mixed lineage kinase 3 (MLK3) and c-Jun N-terminal kinase (JNK) (24,32), and the ER stress response (36,37) are key cellular pathways that mediate proapoptotic signaling initiated by toxic saturated free fatty acids and in the steatotic liver (38). Sphingolipids, too, are elevated in NASH (25), and C16:0 ceramide has recently been linked to the pathophysiology of NASH (39); therefore, we discuss these pathways and concepts below.…”
mentioning
confidence: 99%
“…Accumulating evidence suggests that the MLK-JNK signaling pathway induces inflammation of metabolic tissues and contributes to impaired glucose homeostasis and decreased insulin sensitivity (33)(34)(35)(36)(37)(38). In the beta cell, cross-talk between MLK-JNK and insulin-AKT signaling determines the balance between dysfunction/death and survival, highlighting the importance of mechanisms that can fine tune and tip the balance toward JNK or AKT activity.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported previously that MLK3 -/-mice are protected against liver injury, fibrosis, and inflammation in a murine model of NASH-inducing diet (22,23). We also demonstrated that hepatocytes under lipotoxic stress release chemotactic extracellular vesicles (EVs) by an MLK3-dependent mechanism (23); these vesicles are enriched with the potent macrophage chemotactic ligand (C-X-C motif) ligand 10 (CXCL10), expression of which is regulated by MLK3 in hepatocytes (11).…”
Section: Introductionmentioning
confidence: 99%
“…Bolstered by our data supporting MLK3 as a crucial proinflammatory and proapoptotic mediator in our preclinical in vitro and in vivo model of NASH (22,23), we elected to test the protective effect of the MLK3 pharmacological inhibitor URMC099 in our murine model of diet-induced NASH and obesity. URMC099 is a selective small-molecule MLK3 pharmacological inhibitor that was developed for human use.…”
Section: Introductionmentioning
confidence: 99%